Investigating Albendazole Desmotropes by Solid-State NMR Spectroscopy - Chattah, Ana Karina (2015)
Characterization of the molecular structure and physicochemical solid-state properties of the solid forms of pharmaceutical compounds is a key requirement for successful commercialization as potential active ingredients in drug products. These properties can ultimately have a critical effect on the solubility and bioavailability of the final drug product. Here, the desmotropy of Albendazole forms I and II was investigated at the atomic level. Ultrafast magic angle spinning (MAS) solid-state nuclear magnetic resonance (NMR) spectroscopy, together with powder X-ray diffraction, thermal analysis, and Fourier transform infrared spectroscopy, were performed on polycrystalline samples of the two solids in order to fully characterize and distinguish the two forms. High-resolution one-dimensional 1H, 13C, and 15N together with two-dimensional 1H/1H single quantum-single quantum, 1H/1H single quantum-double quantum, and 1H/13C chemical shift correlation solid-state NMR experiments under MAS conditions were extensively used to decipher the intramolecular and intermolecular hydrogen bonding interactions present in both solid forms. These experiments enabled the unequivocal identification of the tautomers of each desmotrope. Our results also revealed that both solid forms may be described as dimeric structures, with different intermolecular hydrogen bonds connecting the tautomers in each dimer.